Budaya Masyarakat Yang Berhubungan Dengan Pernikahan Dini - Kusumastuti, Bektienadila; Qomaruddin, Mochammad Bagus (Universitas Tribhuwana Tunggadewi, 2023)
Indonesia ranks seventh in the world for cases of early marriage and the second highest after Cambodia in Southeast Asia. Early marriage occurs in women less than 21 years and men less than 25 years, which poses a health risk for women because it can experience complications of pregnancy and childbirth and even cause maternal and infant death. The purpose of this study was to determine the culture of the developing community as a factor in the occurrence of early marriage. This research design is quantitative using cross-sectional, with a sample of 72 people in Karangrejo District in June 2022. The sample recruited randomly using simple random sampling. The data obtained by distributing questionnaires to respondents and data analysis using the Chi-Square statistical test. Based on the results of the study, there is a significant relationship between community culture and the occurrence of early marriage (p-value = 0.028). Community culture is related to early marriage, so the community and parents pay more attention to the impact of early marriage on their children. Therefore, it is necessary to educate parents and society about the risks of early marriage.